Correction to: The antiangiogenic activities of ethanolic crude extracts of four Salvia species - Malek Zihlif; Fatma Afifi; Rana Abu-Dahab; Amin Malik Shah Abdul Majid; Hamza Somrain; Mohanad M. Saleh; Zeyad D. Nassar; Randa Naffa (BMC, 2018)
Correction After the publication [1] it came to the attention of the authors that one of the co-authors was incorrectly included as Hamza Somrain. The correct spelling is as follows: Hamzeh Sumrein.